2021
DOI: 10.1186/s13765-021-00608-3
|View full text |Cite
|
Sign up to set email alerts
|

Determination of antioxidant activity and phenolic compounds for basic standardization of Turkish propolis

Abstract: This study aimed to determine the standard amount of antioxidant content and compounds of the propolis for the standardization of propolis. For this purpose, the total flavonoids, total phenolic, CUPRAC antioxidant capacity content and the diversity of phenolic and flavonoid components of these propolis samples were found by HPLC determined at the 23 propolis samples which were collected different regions of Turkey. Beside that, the similarities and differences of these 23 provinces to each other according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…Our results indicated that content of total phenolic compounds and flavonoids could be related to the type of vegetation predominant in the locations where the propolis was collected. The results obtained in this study coincide with those reported by other authors for classification and authentication of propolis from stingless bees collected in tropical forests in Asia and Brazil [ 11 , 13 , 44 , 45 , 46 , 47 ]. The correlation analysis between the contents of phenols and flavonoids was significantly negative.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results indicated that content of total phenolic compounds and flavonoids could be related to the type of vegetation predominant in the locations where the propolis was collected. The results obtained in this study coincide with those reported by other authors for classification and authentication of propolis from stingless bees collected in tropical forests in Asia and Brazil [ 11 , 13 , 44 , 45 , 46 , 47 ]. The correlation analysis between the contents of phenols and flavonoids was significantly negative.…”
Section: Discussionsupporting
confidence: 92%
“…The correlation analysis between the contents of phenols and flavonoids was significantly negative. A study conducted on propolis stingless bees from Malaysia indicated the opposite behavior [ 45 ]. In this sense, the differences observed in our study may be due to factors such as bee species, predominant vegetation, and extraction methods.…”
Section: Discussionmentioning
confidence: 99%
“…From our study, the reported quantities of phytochemicals and bioactivities are in accordance with those earlier reported 4,15–19 . Previous studies on total phenols have been performed in different regions of the world, for example, in Algeria 0.8–9.0 mg GAE/g, 20 Mexico 68–500 mg GAE/g, 21 Spain 200–340 mg GAE/g, 22 Turkey 34.5–259.4 mg GAE/g 23 and on total flavonoids in Turkey 21.3–152.6 mg QE/g, and Mexico 13–379 mg QE/g, Algeria 0.6–3.5. All these results are consistent with our data, except for some variation because of the influence of vegetation on the chemical properties of propolis 24 .…”
Section: Discussionsupporting
confidence: 91%
“…Polyphenols are the main constituents of propolis that have health-promoting properties, and propolis has been reported as the bee product containing the highest number of phenolic compounds [ 56 ]. Polyphenols, such as quercetin [ 57 ] and catechin [ 12 ], that have shown protective effects against this specific carcinogen, have been reported in this bee product. In addition, CAPE, known as a key anticancer component [ 58 ], has been ascribed as the most valuable biologically active compound in propolis for its several biological and pharmacological properties [ 56 ].…”
Section: Resultsmentioning
confidence: 99%